Investigation on dynamic stability and aeroelastic characteristics of composite curved pipes with any yawed angle - Chen, Fujiang; Chen, Junying; Duan, Rongqian; Habibi, Mostafa; Khadimallah, Mohamed Amine (Composite structures, 2022)
For the first time, in the current work, a dynamic stability analysis of a tilted curved pipe in a supersonic airflow under thermal loading is presented. The heat-transfer continuum problem is used for simulating the thermal environment conditions. The tilted pipe is reinforced by carbon nanotube agglomerations (CNTAs). For simulating the displacement fields of the current structure, Quasi-2D refined high order shear deformation theory is studied. The verification segment is divided into two parts. In the first and second sections, the credibility of the results of this study are confirmed by the results extracted using COMSOL multiphysics software and published articles in the literature, respectively. The results show that Mach number, hydrodynamic pressure, temperature change, yaw angle, and geometry properties of the current structure have a significant impact on the frequency information of the tilted curved pipe reinforced by CNTAs in supersonic airflow. One of the presented results is that the effects from volume fraction of clusters in the representative value element, amount of CNTs located outside the clusters, and the highest value related to the volume fraction of the CNT, parameters on the supersonic airflow characteristics of the system are more considerable at the higher value of the length to radius ratio of the pipe.